Design and simulation of propeller for high speed mud boat - Muhamad Effendi Azamudin (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
As part of the nation that surrounded by the sea and mat this cost, the current high speed mud boat that were used by Maritime Malaysia were sole made to working on the water. The purpose of this research is to design the propeller that could woking in two medium which is water and mud. There is many type of propeller that were now available and some are still in the research and development process, among those this research will focus on designing the fixed pitch acceleration duct type propeller and contra rotating propeller at which both type are well astabished.